Penerapan Metode HEAT Dalam Penanganan Komplain di Front Office Luwansa Beach Resort - Yohanes Paulus Hanny Wadhi; Hersanius Kurnia Peong (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2026)
This research was motivated by guest complaints regarding the facilities and services at Luwansa Beach Resort, which were mostly conveyed via online platforms. The aim of the research is to evaluate the effectiveness of implementing the HEAT (Hear, Empathize, Apologize, Take Action) method in handling complaints in the Front Office department. The research uses a qualitative approach through interviews with staff and guests, as well as direct observation of the complaint handling process. The research results show that the HEAT method is generally effective in improving service quality and building positive relationships with guests. However, obstacles are still found in the form of inconsistencies in implementing SOPs, limited communication with foreign guests, and limited staff authority in decision making. These obstacles have an impact on delays in handling complaints and reduce the effectiveness of responses. It is hoped that these findings will provide applicable input for hotel management in improving the service system.